Interaction of air shock waves with parachute stoppings in mine explosions - Mazepa, E. E. (Combustion, explosion, and shock waves)
This paper presents the results of mathematical modeling of the propagation of air shock waves during methane explosion in mine workings taking into account their interaction with prefabricated parachute stoppings. Parachute stoppings are able to reduce the shock-wave intensity when the intensity of the incoming shock wave does not exceed the critical failure pressure of the stopping. The gas-dynamic method of calculating explosion-proof distances allows one to take into account parachute stoppings installed in various places of workings and to calculate the parameters of shock waves that have passed beyond the stopping.